United Nations endorsement and support for human rights: An experiment on women's rights in Pakistan. (May 2021) - Anjum, Gulnaz; Chilton, Adam; Usman, Zahid
The United Nations is one of the organizations charged with developing and promoting international human rights law. One of the primary ways that the United Nations tries to do that is by regularly reviewing the human rights practices of member states and then recommending new policies for that state to implement. Although this expends considerable resources, a number of obstacles have made it difficult to empirically assess whether the UN's review process actually causes countries to improve their human rights practices. To study this topic, we conducted an experiment in Pakistan that tested whether respondents were more likely to support policies aimed at improving women's rights when they learned that the reforms were proposed by the United Nations. Our results indicate that the respondents who were randomly informed of the United Nations endorsement not only expressed higher support for the policy reforms, but also were more likely to express willingness to 'mobilize' in ways that would help the reforms be implemented. Our treatment did not have any effect, however, on respondents that did not already have confidence in the United Nations. This suggests that the international human rights regime may only be able to aid domestic reformers when there is already faith in those institutions.